COMPARATIVE ANALYSIS OF Z-SCORE AND SPRINGATE ALTMAN MODELS ON REGISTERED COAL COMPANIES BEI IN - Caroline, Lisda; Laturette, Kazia (Research In Management and Accounting (RIMA), 2019)
Subsector coal mining sector experienced a decrease from the years 2011-2015, if the company fails to carry out operations to generate a profit, then this may lead to bankruptcy. The purpose of this study was to determine whether there are differences in the potential bankruptcy of the Altman Z-score models and models Springate, as well as to determine the model of bankruptcy is most appropriate for the coal company listed on the Indonesia Stock Exchange in 2011 to 2015. This research method is quantitative secondary data is the data from this study. The results of this study, based on the results of hypothesis testing with different test paired samples t-test mennjukkan that there are differences in the potential bankruptcy of the Altman Z-score models and models Springate. Then, based on the calculation and oengamatan writer, a model that can assess more fair and appropriate for the coal company listed on the Indonesia Stock Exchange period 2011 - 2015 is the model of the Altman Z-score.